Online fortune telling system - Kok, Shi Hui (2015)
Palmistry is the claim of characterization and foretelling the future through the study of the palm, also known as palm reading. It has been used for centuries in different cultures, and there are many variations of the interpretation. Palm Reading is considered the most fundamental technique in Chinese fortunetelling. In the old days when a person's birthday is unavailable or inaccurate for horoscope analysis, a palm reading master can study the person's hand to foretell future and traits. The analysis is based on the lines and creases on the palm, and characteristics of the arm, hand, palm, finger, and fingernail. The study of Chinese palm reading can be tracked all the way back to three thousand years ago. Today, it still remains a commonly used fortunetelling technique in China, Taiwan, and Hong Kong. The application will look into traditional Chinese palmistry, the algorithm used to extract the 3 major palm lines and bringing it to Android mobile platform. The project consist the early development stages of the Android application that uses the camera and storage of the phone to tell the fortune of the user. This report will talk more in details about the development of the android application, the research done to development the applications, the problems faced while developing this application and the outcome of the application. This report also include the conclusion of the project and future recommendations that can be carried out to improve on the application.